FOOT MASSAGING AND RELAXATION PHYSIOLOGICAL RESPONSE OF CANCER PATIENTS - T. Najafi Ghezeljeh; F. Rahimiha (Iran University of Medical Sciences, 2004)
Discomfort is one of the main complaints, and a common problem of cancer patients. Higher oxygen consumption, respiratory and pulse rates as well as blood pressure and muscle tension are physiologic responses to discomfort. Providing the patients with the massage leads to relaxation, comfort and eventually will change physiological responses. Determining the effects of foot massaging on relaxation physiological responses of hospitalized women with cancer, a crossover clinical trial study was conducted. So, 75 women all over 18 years, selected sequentially were divided in two groups, and also in a 3rd part situation named "controlled". Vital signs of groups were measured after 10 minutes of massaging, meanwhile in controlled situation patients were advised just to lye on their beds comfortably for 20 to 30 minutes, and then their vital signs were measured and recorded. Findings showed that there were statistically significant differences in pulse and, respiratory rates, systolic and diastolic blood pressures of subjects with foot massage (1) and without massage and between subjects with foot massage (1) and (2) (except for systolic and diastolic blood pressure). In other words, massaging declined pulse and respiratory rates, systolic and diastolic blood pressures. As repeated foot massage provided more reduction in pulse and respiratory rates, there weren't statistically significant differences in systolic and diastolic blood pressure reduction. Variables trends of change were statistically significant (p<0/000), or, all variables decreased from controlled situation to massage (2) session. So, according to the results, nurses can use massage for providing relaxation and decreasing discomfort in cancer patients. Similar researches is recommended to be conducted for men.